Predictors of Complicated Grief: A Systematic Review of Empirical Studies - Lobb, Elizabeth; Kristjanson, Linda; Aoun, Samar; Monterosso, Leanne; Halkett, Georgia; Davies, A. (Routledge, 2010)
A systematic review of the literature on predictors of complicated grief (CG) was undertaken with the aim of clarifying the current knowledge and to inform future planning and work in CG following bereavement. Predictors of CG prior to the death include previous loss, exposure to trauma, a previous psychiatric history, attachment style, and the relationship to the deceased. Factors associated with the death include violent death, the quality of the caregiving or dying experience, close kinship relationship to the deceased, marital closeness and dependency, and lack of preparation for the death. Perceived social support played a key role after death, along with cognitive appraisals and high distress at the time of the death. Inconsistent definitions of CG and measurement tools were noted in the earlier studies reviewed. Limitations identified in the studies included use of cross-sectional designs, heterogeneous samples, high attrition, demographic differences between cases and controls, differences in length of time since death, and differences in types of death experienced. Notwithstanding these limitations, some consistent findings have emerged. Further research into conceptualizations of CG in terms of attachment theory and constructivist and cognitive-behavioral concepts of finding purpose and meaning after bereavement is warranted.